The natural product chitosan enhances the anti-tumor activity of natural killer cells by activating dendritic cells. (3rd June 2018) - Li, Xinxin; Dong, Wenjuan; Nalin, Ansel P.; Wang, Yufeng; Pan, Pan; Xu, Bo; Zhang, Yibo; Tun, Steven; Zhang, Jianying; Wang, Li-Shu; He, Xiaoming; Caligiuri, Michael A.; et al.
ABSTRACT: Natural products comprise an important class of biologically active molecules. Many of these compounds derived from natural sources exhibit specific physiologic or biochemical effects. An example of a natural product is chitosan, which is enriched in the shells of certain seafood that are frequently consumed worldwide. Like other natural products, chitosan has the potential for applications in clinical medicine and perhaps in cancer therapy. Toward this end, the immunomodulatory or anti-cancer properties of chitosan have yet to be reported. In this study, we discovered that chitosan enhanced the anti-tumor activity of natural killer (NK) cells by activating dendritic cells (DCs). In the presence of DCs, chitosan augmented IFN-γ production by human NK cells. Mechanistically, chitosan activated DCs to express pro-inflammatory cytokines such as interleukin (IL)-12 and IL-15, which in turn activated the STAT4 and NF-κB signaling pathways, respectively, in NK cells. Moreover, chitosan promoted NK cell survival, and also enhanced NK cell cytotoxicity against leukemia cells. Finally, a related in vivo study demonstrated that chitosan activated NK cells against B16F10 tumor cells in an immunocompetent syngeneic murine melanoma model. This effect was accompanied by in vivo upregulation of IL-12 and IL-15 in DCs, as well as increased IFN-γ production and cytolytic degranulation in NK cells. Collectively, our results demonstrate that chitosan activates DCs leading to enhanced capacity for immune surveillance by NK cells. We believe that our study has future clinical applications for chitosan in the prevention or treatment of cancer and infectious diseases.